PERAN MOTIVASI DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK - Permatasari, Dian Anggraini; Efendi, David (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
Taxpayer’s compliance due to their awareness may be influenced by two factors, namely motivation and level of education. Therefore, this research aimed to examine and analyse whether motivation and level of education affected personal taxpayer’s compliance or not. The research was quantitive. Furthermore, the data collection technique used a random sampling technique, in which every member of the population had the same opportunity to be taken as a sample. The sample was taken randomly whitout considering strata within the population. In line with that, there were 90 respondents of personal taxpayers in the sample. Moreover, the data analysis technique used multiple linear regression. The research result concluded that motivation had a positive effect on personal taxpayers’ compliance. This shows that the higher motivation to pay taxes, the higher compliance of personal taxpayers’. Likewise, the level of education had a positive effect on personal taxpayers’ compliance. This shows that the higher level of education, the higher compliance of individual taxpayers’.